The Problem of Story: Criminal Evidence, Affect, and Sense-making. Issue 4 (1st October 2020) - Rossmanith, Kate
ABSTRACT: Poignant, complex relationships exist between forensic evidence, people's efforts to comprehend painful events, and the role of story-structures and storytelling. While there is intense public interest in criminal cases, and while law and criminology research acknowledges the centrality of narrative in criminal justice matters, significantly more research is needed to better understand the complicated intersections between criminal procedure, sense-making, and affect. The field of life writing has much to offer inquiry into legal and judicial processes. This article considers how life writing might be deployed as a research method to study dimensions of criminal justice otherwise overlooked. Using unsolved homicide as a case study, it examines how people's framing of justice processes in narrative terms powerfully influences the way unresolved cases are experienced. It then suggests how life writing forms may offer ways to illuminate and critique people's problematic relationships to 'story', and how they can animate people's complex relationships between extreme happenings and everyday objects and places. In this way, the article reveals the potential of life writing to significantly advance knowledge in institutional fields that have so far traditionally been studied using other methods.